(untitled) (Nonconventional Technologies Review, 2021)
The paper presents an innovative technique for manufacturing glass foams from recycled glass waste at room temperature by using aluminum powder and an aqueous solution of calcium hydroxide. The physical, thermal, mechanical and morphological characteristics of the foamed products (porosity between 82.9-86.2%, thermal conductivity in the range 0.061-0.081 W/m·K and compressive strength between 1.15-1.28 MPa) were similar to those of the foams manufactured by sintering at high temperatures. Glass foams produced by this new technique are suitable for use as thermal insulation materials for buildings.